SOCIAL AND SPIRITUAL ANALYSIS OF THE CONDITIONS FOR ENSURING PEACE, SECURITY AND STABILITY IN UZBEKISTAN (Neo Scientific Peer Reviewed Journal, 2024)
Ensuring peace and stability among people is becoming a very important issue in the complex era of the current globalization processes. In this article, the importance of ensuring peace, security and stability in Uzbekistan, its conditions and influence on the development of our society are analyzed based on the works of the Honorable first President I.A. Karimov and the current President Sh.M. Mirziyoyev, as well as the spiritual values of the people of our country.